THE INFLUENCE OF CULTURE AND RELIGION ON GENDER INEQUALITY AND IT IMPLICATIONS ON WOMEN EMPOWERMENT - GRACE ETIM-JAMES (International Studies Journal)
Gender is intrinsically linked to culture that is why culture has continued to be one of the major determinants of gender Inequality. Gender defines the norms and values regarding masculine and feminine roles and behaviour, which is a major threshold of gender inequality. Gender is not dependent on biological sex and sexual orientation, although it only has an unstable relationship with biological sex because it can influence how individual view and participate in gender roles. Culture has always been the main determinant in both domestic and communal activities. Religion focuses on patriarchy and androcentrism. Religion acts as an oppressive deceptive mechanism used by the patriarchal society to exploit women based on defined gender roles and not by biological differences. This paper sets out to differentiate gender and sex as two different entities, focusing on how gender is heavily influenced by cultural and religious expectations and not by biological differences, which in turn creates gender roles and these gender roles further energizes gender inequality. In the light of the above assertions, possible recommendations to eliminate or drastically reduce gender inequality were suggested.